SAT0393 DISCREPANCY IN THE CARDIOVASCULAR RISK SEVERITY CALCULATED USING DIFFERENT RATING SCALES IN PATIENTS WITH AXIAL SPONDYLOARTHRITIS. (13th June 2020) - Vasilenko, E.; Mazurov, V.; Samigullina, R.; Dadalova, A.; Gaydukova, I.
Abstract : Background: Cardiovascular risk (CVR) in patients (pts) with axial spondyloarthritis (axSpA) exceed the populational level. However, it remains unclear, which of the cardiovascular risk assessment systems is the most accurate in cases of chronic inflammation.. Objectives: of the current study were to assess the CVR in pts with axSpA and to compare different cardiovascular risk scales in these pts. Methods: The study included 118 patients at the age of 25-65 years with diagnosis of axSpA fulfilling ASAS criteria (2009) from St. Petersburg' axSpA register. Three indices of cardiovascular risk evaluation (Systematic COronary Risk Evaluation (SCORE) with increasing coefficient 1.5 for inflammatory diseases, Reynolds Risk Score (RRS), and the third modification of QRESEARCH Cardiovascular Risk Algorithm (QRISK3) were calculated. For the pts below 40 years old only QRISK3 was calculated. Results: Mean age of the pts was 44.3±11.1 years; 91(77.1%) pts were males, HLA-B27 positive – 83 (70.3%) of the pts; mean disease duration 13.0±8.3 years. Mean value of SCORE was 2.78±1.89%, of RRS – 5.28±3.31%, of QRISK3 – 7.91±3.8% (figure 1 ). Cronbach's alpha for the scales was 0.873. High CVR (≥5 %) was found in 14 (11, 7%) of the pts according to the SCORE, in 65 (55, 1%) of the pts according to the RRS, and in 81 (69%) of the pts according to the QRISK3. Ranking of CVR severity did not match in SCORE and QRISK3 indices in 83.72% of cases, in SCORE and RRS – in 51.16% of cases, and in QRISK3 and RRS in 8% of cases. The SCORE index showed the lower values of the expected risk as compared to the QRISK3 and RRS (figure1). In axSpA pts at age 25-40 years old (n=46, mean age 32.6±4.0 years, males 36 (78.3%)), mean value of QRISK3 was 1.16±0.99 %; in 14 from 46 (30.4%) of those pts increased CVR was registered (figure 2 ). Conclusion: There was a discrepancy in the severity of CVR calculated using different rating scales in axSpA patients. The SCORE index showed lower values of CVR as compared to the QRISK3 and RRS, which hypothetically could be the consequence of CVR underestimation. QRISK3 demonstrated the highest CVR and was the only index useful in pts below 40 years old. To exclude hyper- or underestimation of CVR calculation more data about CVR calculations and frequency of CV events, occurring in axSpA patients are needed. Disclosure of Interests: Elizaveta Vasilenko: None declared, V Mazurov: None declared, Ruzana Samigullina: None declared, Anna Dadalova: None declared, Inna Gaydukova Grant/research support from: JSC BIOCAD, Speakers bureau: Pfizer, Novartis, AbbVie, JSC BIOCAD, Сelgene, MSD, Sanofi